2017
DOI: 10.1096/fj.201600687rrr
|View full text |Cite
|
Sign up to set email alerts
|

Fluid shear stress increases transepithelial transport of Ca 2+ in ciliated distal convoluted and connecting tubule cells

Abstract: In kidney, transcellular transport of Ca is mediated by transient receptor potential vanilloid 5 and Na-Ca exchanger 1 proteins in distal convoluted and connecting tubules (DCTs and CNTs, respectively). It is not yet understood how DCT/CNT cells can adapt to differences in tubular flow rate and, consequently, Ca load. This study aims to elucidate the molecular mechanisms by which DCT/CNT cells sense fluid dynamics to control transepithelial Ca reabsorption and whether their primary cilia play an active role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 59 publications
(96 reference statements)
1
20
0
Order By: Relevance
“…Alternatively, the lack of IFT40 function could affect cell structure or differentiation, which indirectly modifies Mg 2+ transport due to potential altered channel localization or function. Our finding that primary cilia are not involved in FSS‐activated cellular Mg 2+ uptake in DCT is in line with previous studies showing no relation between flow sensing by primary cilia and CNT Ca 2+ transepithelial transport or the electrolyte transport transcriptome in the CD (21, 27). Possibly, the plethora of functions attributed to primary cilia sensing do not encompass electrolyte transport or it is limited to the ability to increase intracellular Ca 2+ levels, a function that is also under debate (53).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Alternatively, the lack of IFT40 function could affect cell structure or differentiation, which indirectly modifies Mg 2+ transport due to potential altered channel localization or function. Our finding that primary cilia are not involved in FSS‐activated cellular Mg 2+ uptake in DCT is in line with previous studies showing no relation between flow sensing by primary cilia and CNT Ca 2+ transepithelial transport or the electrolyte transport transcriptome in the CD (21, 27). Possibly, the plethora of functions attributed to primary cilia sensing do not encompass electrolyte transport or it is limited to the ability to increase intracellular Ca 2+ levels, a function that is also under debate (53).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies in primary DCT/CNT cultures using oscillatory flow have shown that transepithelial Ca 2+ transport is facilitated by an up‐regulation of the expression of calciotropic genes such as Trpv5 and Slc8a1 , which encode an apical Ca 2+ channel and a basolateral Na + ‐Ca 2+ exchanger, respectively (21). However, in vivo , prourinary flow is of laminar nature (17, 54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects of fluid flow on CD electrolyte handling lead to the conclusion that renal tubular cells respond to fluid flow to regulate the activity and abundance of electrolyte channels and transporters in the CD. In fact, this postulation has been demonstrated in the connecting tubule of the nephron, where fluid shear stress regulates the gene expression of transient receptor potential cation channel subfamily V (Trpv5) and solute carrier family 8 member a1 (Slc8a1), coding the proteins that allow transepithelial Ca 2+ transport in this segment of the nephron (14).…”
mentioning
confidence: 99%
“…An important mechanical stimulus for renal epithelial cells is FSS. In tubular epithelial cells cultured in vitro, physiological levels of FSS alters cytoskeletal organization and transport proteins resulting in enhanced epithelial cell phenotype (Duan, Weinstein, Weinbaum, & Wang, ; Mohammed et al, ; Raghavan, Rbaibi, Pastor‐Soler, Carattino, & Weisz, ). On the other hand, pathological levels of FSS may be responsible for losing of epithelial characteristics that may account for the progression of chronic kidney disease (Grabias & Konstantopoulos, ; Maggiorani et al, ).…”
Section: Introductionmentioning
confidence: 99%